Componentes de produção da cultura do cártamo (Carthamus tinctorius L.) em Latossolo argiloso sob estados de compactação - Montiel, Caroline Beal (2019)
Safflower has been studied as an alternative for the production of biofuel because of its high potential in oil production and also the search for sustainable production. The objective of this work was to evaluate the root growth and development of the safflower culture when submitted to 5 levels of soil compaction in a clayey Oxisol in the western region of Paraná. The experiment was conducted in two stages: the first stage in a greenhouse and the second stage in the field, in an area located at the State University of the West Paraná campus of Cascavel - PR. The treatments consisted of 5 densities, being 1,1; 1,2; 1,3; 1,4 and 1,5 Mg m-3 and 4 replications, with a completely randomized design in greenhouse. In the field cultivation, four treatments were obtained, P0 = 0 past, P1 = one pass, P3 = three passes and P5 = five passes, with experimental design in strips. The variables analyzed were: plant height, stem diameter, dry and fresh mass weight of plant and root and root system length. Statistical analysis was performed through analysis of variance (ANOVA), and the means of treatments were compared by the Tukey test at 5% significance. Soil density values of 1,2 Mg m-3 or higher are restrictive to safflower root growth. The measurement of the weight gain and the drying of plants of the soil to the growth and the state of compaction of the soil.